(untitled) (Research, Society and Development, 2018)
In this work we present an investigation on the analysis of an investigative teaching strategy in the training of chemistry professors at a federal public university in the State of São Paulo, with seven undergraduate students in chemistry during a four - month period. The methodology in the study is qualitative in nature of the discourse analysis type. The data are composed of the praxis analysis of the teaching lesson plan in the discipline Chemical Experimentation and Teaching (CET). The obtained data reveal the enrichment in the initial formation process, motivating the participation and commitment of the students with the activities. The investigative teaching was distinguished by involving the good planning of the teacher and students in the construction of scientific knowledge, and that it is possible as a strategy of the application of didactic procedure in the teaching work.